Efeitos da faixa de amplitude de conhecimento de performance na faixa de aquisição de uma habilidade motora do judô - Cleber de Souza Lopes (2017)
The bandwidth knowledge of performance knowledge is an arrangement where feedback is directly related to the attempts that do not reach a performance range in relation to the goal. Considering that the effect of different bandwidths directly affect the consolidation of a sporting ability, one group received feedback in a bandwidth of smaller error range, called the narrow bandwidth, and a group that received feedback in a bandwidth of greater error range, denominated wide bandwidth. The objective of the present study was to verify the effects of the bandwidth in the acquisition of a Judo motor skill. The task used in this experiment was the O Soto Gari throw. Thirty-six volunteers were randomly assigned to three experimental groups: control group that received performance knowledge in all trials; WBG group that received knowledge of performance in a wide bandwidth; NBG group that received performance knowledge in a narrow bandwidth. The experiment consisted of an entrance test, acquisition phase, post test and retention test. The results of the experiment showed that the control group presented worse results when compared to the other bandwidths groups. Also, the wide bandwidth helped in the changes of performance and pattern of the movement, favoring the improvement of the consistency and precision. The wide KP bandwidth aided in learning complex motor skills, and that the narrow bandwidth, while helping to change the pattern of execution, was not enough to result in changes in performance. In summary, the study concluded that the wide KP bandwidth was more adequate for sports learning. Taken together these findings show that the combination of a lower KP supply frequency, the effect of qualitative information on performance, coupled with an optimal intertrial interval, was the key to the effects of the KP bandwidth on the acquisition of a complex task with specific demands like the Judo throw: O Soto Gari